Expression, purification and characterisation of the recombinant soluble receptor for advanced glycosylation end products (sRAGE) - Chandler, David James (Curtin University, 2014)
The soluble receptor for advanced glycation end products, otherwise known as RAGE, is activated by a myriad of molecules, resulting in the progression of chronic diseases such as Alzheimer's disease, diabetes and cancer. This study genetically engineered bacterial and insect cells to produce various forms of RAGE and the molecules that activate it. These proteins were purified, shown to be functional and now form a platform for research into the progression of these chronic diseases.